2018
DOI: 10.3390/ijerph15040825
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Hidden Hazards: Community-Led Spatial Data Collection of Street-Level Environmental Stressors in a Degraded, Urban Watershed

Abstract: We utilized a participatory mapping approach to collect point locations, photographs, and descriptive data about select built environment stressors identified and prioritized by community residents living in the Proctor Creek Watershed, a degraded, urban watershed in Northwest Atlanta, Georgia. Residents (watershed researchers) used an indicator identification framework to select three watershed stressors that influence urban livability: standing water, illegal dumping on land and in surface water, and faulty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 33 publications
0
40
0
1
Order By: Relevance
“…Reported food access issues are consistent with much research [68,69]. Residents reporting illegal dumping are right to be concerned, as it compromises safety, environmental health, soil, the water table, plants, animals, and property values [70,71]. Additionally, as residents noted in their discussion of concerns about trees being removed, trees can be effective at improving air quality by reducing harmful air pollutants [72].…”
Section: Discussionmentioning
confidence: 69%
“…Reported food access issues are consistent with much research [68,69]. Residents reporting illegal dumping are right to be concerned, as it compromises safety, environmental health, soil, the water table, plants, animals, and property values [70,71]. Additionally, as residents noted in their discussion of concerns about trees being removed, trees can be effective at improving air quality by reducing harmful air pollutants [72].…”
Section: Discussionmentioning
confidence: 69%
“…The overwhelmingly African American and poor residents who remained have had to contend with the pullout of private capital, eroding infrastructure, high rates of vacant and abandoned properties, and crime rates. 30,31,32 English Avenue earned the infamous moniker, ''The Bluff'' in recent decades, due to the openly visible heroin trading that occurred there until recently. 33 Related, Atlanta police raided the house of 92-year old Kathryn Johnston in 2006, fatally wounding her, when they mistook the residence for a drug house.…”
Section: Articulation Of Proctor Creek Valuesmentioning
confidence: 99%
“…Relevant to the present study, they also found that civic engagement, in the form of voting and community organizing, did not lessen blighted conditions. However, Osborne Jelks et al (2018) contend that in Atlanta, resident-led monitoring and cleanup of neighborhoods is a more effective recourse for blight remediation than generalized civic participation. This kind of civic engagement goes beyond petitioning municipal authorities for redress; rather, it places community activists on the ground, physically in communities to not only call out blighted conditions but also to inventory and remediate dereliction (Greenberg, 2001;Osborne Jelks, 2008;Osborne Jelks et al, 2018).…”
Section: Literature Review Atlanta's Blight Problemmentioning
confidence: 99%
“…However, Osborne Jelks et al (2018) contend that in Atlanta, resident-led monitoring and cleanup of neighborhoods is a more effective recourse for blight remediation than generalized civic participation. This kind of civic engagement goes beyond petitioning municipal authorities for redress; rather, it places community activists on the ground, physically in communities to not only call out blighted conditions but also to inventory and remediate dereliction (Greenberg, 2001;Osborne Jelks, 2008;Osborne Jelks et al, 2018). Of course, residents are limited in the impact they can effect, but this sort of activism places people in out-of-doors spaces where their activities can be witnessed by others.…”
Section: Literature Review Atlanta's Blight Problemmentioning
confidence: 99%